Multiscale computational modeling of 3D printed continuous Fiber reinforced polymer composites - Xin Li (Scientific Reports)
Abstract Printing parameters significantly affect elastic properties of 3DP-CFRPCs. Testing these experimentally would require time and would cost much. Computational material modeling is an adequate technique for studying how 3DP-CFRPCs would behave in varying printing conditions. Material modeling was employed in this work to analyze how elastic properties in 3DP-CFRPCs vary with printing conditions. Pores in the matrix were homogenized by Mori-Tanaka method to calculate bead flexibility. Elastic modulus was found by finite element modeling of Representative Volume Elements (RVEs) with microstructure and printing conditions taken into account. Elastic properties differed in differently microstructured models with more disparity in more intricate structures than in more basic ones. Computational modeling provided insight to elastic properties of 3DP-CFRPCs in varied printing conditions. The results also show that thickness of the layers and interfacial properties determine the elastic properties to a great extent, such that higher thickness of the layers and stronger interfacial bonding lead to higher stiffness. The model also correctly simulated behavior of 3DP-CFRPCs when different printing parameters were used, with low error compared to experimental results. The impact of layer thickness on the mechanical characteristics of 3DP-CFRPCs was determined to be more substantial compared to the effect of printing temperature. The application of offset layup printing techniques enhanced the elastic properties of 3DP-CFRPCs, with the degree of improvement varying based on the orientation. As the level of porosity increased, the influence of pores situated between beads on the overall stiffness of 3DP-CFRPCs gradually diminished, while the impact of matrix pores on the overall stiffness of 3DP-CFRPCs gradually intensified.